Distribution of Major HLA-A, -B, -DR, and -DQ Loci Potentially Associated with Multiple Sclerosis in a Healthy Population from Southern Morocco - Abir Fguirouche; Fatimazahra Ouahmani; Ikram Brahim; Raja Hazime; Nissrine Louhab; Najib Kissani; Mohamed Chraa; Brahim Admou (Clinics and Practice)
Background: Many factors contribute to the development and the progression of Multiple Sclerosis (MS), including Human Leukocyte Antigen (HLA) molecules. Some of them are considered as predisposing, like DRB1*15, DRB1*13, DRB1*03, DRB1*04, DQB1*06, DQB1*02, while HLA A2, HLA B44, DRB1*11, and DRB1*12 are rather considered as protective. Data about such associations in the Moroccan population remain unknown. The aim of this study was to determine the frequency of HLA class I (A and B) and II (DR and DQ) linked to Multiple Sclerosis (MS) in a healthy population from the South of Morocco. Materials and Methods: A cross-sectional study was carried out over the 2016–2023 period on 685 Moroccan healthy individuals, including 355 males and 330 females. Of the total sample tested, 685 underwent HLA class I typing, of which 305 also benefited from HLA class II typing. HLA class I typing was executed using the CDC (complement dependent cytotoxicity) technique (OneLambda™, Los Angeles CA, USA), and HLA class II typing was performed by either PCR-SSP (sequence-specific primer, OneLambda) or PCR-SSO (sequence-specific oligonucleotides) using the Luminex Xmap (Lifecodes, Immucor, Peachtree, Corners, GA, USA) system. Results: From different HLA molecules potentially predisposing to MS, our investigations showed that DRB1*03, DRB1*13, DRB1*15, DRB1*04, and DQB1*02 were observed in 19.2%, 15.8%, 13.31%, 12.7% and 31% respectively, while the frequency of those considered as protective, namely HLA-A2, HLA-B44, and HLA-DRB1*11 was 23.31%, 9.21% and 10.1% respectively. Conclusions: The findings of our study give evidence that among predisposing HLA class II molecules, DR allele groups were more prevalent, mostly DRB1*03, with also a high frequency of DQB1*06, while HLA-A2 marked the supposed protective specificities. These results need to be supported by complementary studies particularly in MS patients.